2009
DOI: 10.1007/s10439-009-9808-9
|View full text |Cite
|
Sign up to set email alerts
|

Transient Absorption of Inhaled Vapors into a Multilayer Mucus–Tissue–Blood System

Abstract: Previous studies have approximated the absorption of vapors into the walls of the respiratory tract as a steady state process. However, non-dimensional analysis indicates that the absorption of vapors in the conducting airways is time-dependent over the timescale of a breathing cycle. The objective of this study was to evaluate the mass transport of sample chemical species through a simple multilayer system composed of mucus, tissue, and blood components on a transient basis. Individual multilayer models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, 1-D models and experiments clearly show that blood concentrations increase over longer timescales (Kumagai and Matsunaga, 1995). An analytical solution of this system was previously developed by Tian and Longest (2010a) and extended to formulate a CFD boundary condition including the air phase by Tian and Longest (2010b). The analytical solution for the concentration of an absorbed species in the mucus and tissue layers is briefly reviewed below.…”
Section: Analytical Solution For Mass Transport In Mucus and Tissue Lmentioning
confidence: 97%
See 2 more Smart Citations
“…However, 1-D models and experiments clearly show that blood concentrations increase over longer timescales (Kumagai and Matsunaga, 1995). An analytical solution of this system was previously developed by Tian and Longest (2010a) and extended to formulate a CFD boundary condition including the air phase by Tian and Longest (2010b). The analytical solution for the concentration of an absorbed species in the mucus and tissue layers is briefly reviewed below.…”
Section: Analytical Solution For Mass Transport In Mucus and Tissue Lmentioning
confidence: 97%
“…The validity of this assumption has recently been questioned by Longest et al Specifically, Tian and Longest (2010a) showed that transient wall absorption significantly influences uptake over the timescale of one inhalation cycle in the upper airways. For example, Tian and Longest (2010a) found that the uptake of highly and moderately soluble compounds modelled with transient fluxes varied from steady state flux estimates by a factor of ∼30 in nasal and upper TB models after 1 s. As a result, it appears important to consider a time-dependent (or transient) flux value when estimating absorption into the respiratory airway walls. This is especially true in the early stages of exposure where blood concentration values of the inhaled species are near zero.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…25,36 In these studies, the transport of vapor in the tissue has been considered steady state, leading to one-way vapor transport from the air to tissue phases. However, Tian and Longest 41 showed that based on the calculated mass transfer Fourier number, this process is unsteady. Recently, Tian and Longest [39][40][41] published a series of articles on the transient absorption of vapors in respiratory airways using an uptake model that included a mucus-tissue-blood layer.…”
Section: Introductionmentioning
confidence: 95%
“…However, Tian and Longest 41 showed that based on the calculated mass transfer Fourier number, this process is unsteady. Recently, Tian and Longest [39][40][41] published a series of articles on the transient absorption of vapors in respiratory airways using an uptake model that included a mucus-tissue-blood layer. They developed a wall-flux boundary condition for transient absorption that was applied to CFD models of vapor uptake in the respiratory tract.…”
Section: Introductionmentioning
confidence: 95%